Applying insights from implementation and intervention science to improve the evidence base on image and performance-enhancing drugs (IPEDs) interventions. Issue 2 (August 2021) - Bates, Geoff; Vinther, Anders Schmidt
Abstract: Recent decades have seen increased public attention devoted to the use of image and performance-enhancing drugs (IPEDs). As research into the epidemiology and aetiology of IPED use has grown substantially, so has interest amongst scholars and policy makers in developing and implementing a variety of public health interventions that target potential and current IPED users. However, the evidence base on IPED interventions remains underdeveloped and few firm conclusions can be made about their impact. In short, we know very little about whether IPED interventions are appropriate, effective, ineffective, or even harmful, or why and how this is the case. In this article, we make the case for applying recent insights from intervention and implementation science to better assess the problems that require intervention, enhance the development, implementation and evaluation of IPED interventions, and improve the quality and size of the evidence base. This is necessary if we are to develop evidence-based IPED interventions that support good health and avoid the potential to do harm. We begin by discussing the different types of IPED interventions that have been introduced and what we know about their impact from the limited evaluations that have been published to date. We then discuss how methods and frameworks from intervention and implementation science can provide important insights that will greatly enhance the development, implementation, and evaluation of these interventions. Drawing on examples of IPED interventions implemented in a variety of countries we explore how these methods can be applied by those working in this field and identify guidance and tools that support their uptake. We conclude by proposing five key priorities to support the development of a more robust evidence base of IPED interventions that will, ultimately, support an evidence-based public health response to IPED use.